PENGEMBANGAN MATERI AJAR BAHASA ARAB BERBASIS CONNECTED MODEL - Fauzana Annova; Zulmuqim Zulmuqim; Yasmadi Yasmadi (Ensiklopedia of Journal, 2023)
The aim  study was to develop connected model-based Arabic teaching materials at MTsN 1 Padang Pariaman. The research methodology used is Research and development (R&D). This development to internalize Islamic values by connecting prior Arabic material with verses of the Quran and Hadith. The development of prior Arabic language teaching materials by presenting verses of the Quran and Hadith in them is highly expected by students, an average overall need assessment score of 73.93% is obtained,. The results of the expert validation of this development product are 90.5% and the practicality test is also very practical 91.9%. Furthermore, trials were carried out on this development product and also obtained data that the use of this book was very effective with a score of sig (2-tailed) <0.05, which is 0. Therefore it can be concluded that the product of developing connected model based Arabic teaching materials is accepted Furthermore, the textbooks from this development can be disseminated to madrasahs in the vicinity.Keywords: Arabic  Materials, Connected Model, Product of Developing.